Adaptive Differences in Gene Expression in Farm-Impacted Seedbeds of the Native Blue Mussel Mytilus chilensis - Yévenes, Marco; Núñez-Acuña, Gustavo; Gallardo-Escárate, Cristian; Gajardo, Gonzalo (Frontiers in Genetics, 2021)
The study of adaptive population differences is relevant for evolutionary biology, as it evidences the power of selective local forces relative to gene flow in maintaining adaptive phenotypes and their underlying genetic determinants. However, human-mediated hybridization through habitat translocations, a common and recurrent aquaculture practice where hybrids could eventually replace local genotypes, risk populations’ ability to cope with perturbations. The endemic marine mussel Mytilus chilensis supports a booming farming industry in the inner sea of Chiloé Island, southern Chile, which entirely relies on artificially collected seeds from natural beds that are translocated to ecologically different fattening centers. A matter of concern is how farm-impacted seedbeds will potentially cope with environmental shifts and anthropogenic perturbations. This study provides the first de novo transcriptome of M. chilensis; assembled from tissue samples of mantles and gills of individuals collected in ecologically different farm-impacted seedbeds, Cochamó (41°S) and Yaldad (43°S). Both locations and tissue samples differentially expressed transcripts (DETs) in candidate adaptive genes controlling multiple fitness traits, involved with metabolism, genetic and environmental information processing, and cellular processes. From 189,743 consensus contigs assembled: 1,716 (Bonferroni pvalue ≤ 0.05) were DETs detected in different tissues of samples from different locations, 210 of them (fold change ≥ | 100|) in the same tissue of samples from a different location, and 665 (fold change ≥ | 4|) regardless of the tissue in samples from a different location. Site-specific DETs in Cochamó (169) and Yaldad (150) in candidate genes controlling tolerance to temperature and salinity shifts, and biomineralization exhibit a high number of nucleotide genetic variants with regular occurrence (frequency > 99%). This novel M. chilensis transcriptome should help assessing and monitoring the impact of translocations in wild and farm-impacted mussel beds in Chiloé Island. At the same time, it would help designing effective managing practices for conservation, and translocation traceability.